Trial of Cinpanemab in Early Parkinson’s Disease - Lang, Anthony E.; Siderowf, Andrew D.; Macklin, Eric A.; Poewe, Werner; Brooks, David J.; Fernandez, Hubert H.; Rascol, Olivier; Giladi, Nir; Stocchi, Fabrizio; Tanner, Caroline M.; Postuma, Ronald B.; Simon, David K.; et al. (The New England journal of medicine, 2022)
AbstractBackgroundAggregated α-synuclein plays an important role in Parkinson’s disease pathogenesis. Cinpanemab, a human-derived monoclonal antibody that binds to α-synuclein, is being evaluated as a disease-modifying treatment for Parkinson’s disease.MethodsIn a 52-week, multicenter, double-blind, phase 2 trial, we randomly assigned, in a 2:1:2:2 ratio, participants with early Parkinson’s disease to receive intravenous infusions of placebo (control) or cinpanemab at a dose of 250 mg, 1250 mg, or 3500 mg every 4 weeks, followed by an active-treatment dose-blinded extension period for up to 112 weeks. The primary end points were the changes from baseline in the Movement Disorder Society–sponsored revision of the Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) total score (range, 0 to 236, with higher scores indicating worse performance) at weeks 52 and 72. Secondary end points included MDS-UPDRS subscale scores and striatal binding as assessed on dopamine transporter single-photon-emission computed tomography (DaT-SPECT).ResultsOf the 357 enrolled participants, 100 were assigned to the control group, 55 to the 250-mg cinpanemab group, 102 to the 1250-mg group, and 100 to the 3500-mg group. The trial was stopped after the week 72 interim analysis owing to lack of efficacy. The change to week 52 in the MDS-UPDRS score was 10.8 points in the control group, 10.5 points in the 250-mg group, 11.3 points in the 1250-mg group, and 10.9 points in the 3500-mg group (adjusted mean difference vs. control, −0.3 points [95% confidence interval CI, −4.9 to 4.3], P=0.90; 0.5 points [95% CI, −3.3 to 4.3], P=0.80; and 0.1 point [95% CI, −3.8 to 4.0], P=0.97, respectively). The adjusted mean difference at 72 weeks between participants who received cinpanemab through 72 weeks and the pooled group of those who started cinpanemab at 52 weeks was −0.9 points (95% CI, −5.6 to 3.8) for the 250-mg dose, 0.6 points (95% CI, −3.3 to 4.4) for the 1250-mg dose, and −0.8 points (95% CI, −4.6 to 3.0) for the 3500-mg dose. Results for secondary end points were similar to those for the primary end points. DaT-SPECT imaging at week 52 showed no differences between the control group and any cinpanemab group. The most common adverse events with cinpanemab were headache, nasopharyngitis, and falls.ConclusionsIn participants with early Parkinson’s disease, the effects of cinpanemab on clinical measures of disease progression and changes in DaT-SPECT imaging did not differ from those of placebo over a 52-week period. (Funded by Biogen; SPARK ClinicalTrials.gov number, NCT03318523.)